A Duty Cycle Controlled ZVS Buck Converter With Voltage Doubler Type Auxiliary Circuit - Basharat, Sana; Awan, Saeed Ehsan; Akhtar, Rizwan; Hussain, Alamdar; Iqbal, Shahid; Shah, Sayyar Ali; Yuan, Aihua (Frontiers in Energy Research, 2021)
DC-DC converters have wide applications in industries, motor drive circuits, electric vehicles and power supplies. In traditional converters hard switching occurs due to switching losses. This impose constraints on converter’s efficiency which results in heat dissipation and reduction in converter’s life. The proposed converter aims to encounter hard switching problem with the provision of soft switching features. The presented topology is efficient with respect to the features of cost, compact size and durable lifetime of converter topology with the provision of low switching stresses. This research work proposes a novel step down converter with zero voltage switching characteristics. With the use of half bridge inverter switches and series resonant components in auxiliary circuit the target of zero voltage switching and reduction in switching stresses has achieved. The proposed 500W converter is designed to operate at frequency of 100KHz with 300V source input voltage. Output voltage of the converter is 150V.